Value relevance of IFRS 9 adoption: A case study of Indonesian banking companies - Amrie Firmansyah; Lestari Kurniawati; Desrir Miftah; Tjahjo Winarto (Journal of Accounting and Investment, 2023)
Research aims: This study examines the effect of allowance for impairment losses (CKPN) on value relevance.Design/Methodology/Approach: This research employed quantitative data using secondary data from banking financial reports derived from www.idx.co.id during 2019-2021. Also, this study used stock price data sourced from www.finance.yahoo.co.id. The use of data for 2020 was due to the first year of PSAK 71 implementation. While data for 2019 were employed to compare the year before the PSAK 71 implementation, and data for 2021 were used to compare the PSAK 71 implementation in the second year. Data testing was then performed utilizing multiple linear regression analysis for cross-section data.Research findings: This study suggests that CKPN was positively associated with the value relevance of earnings in the first year of PSAK 71 implementation.Theoretical contribution/Originality: This research is expected to complement the financial accounting literature on adopting IFRS 9, especially in Indonesia, which is rarely discussed in previous studies.Practitioner/Policy implication: This study is expected to be employed by the Indonesian Financial Services Authority in improving policies on financial stability in the capital market based on applying financial accounting standards.Research limitation/Implication: This study only employed data on banking sub-sector companies listed on the Indonesia Stock Exchange, which were relatively small in number. Future research can therefore use data from all financial companies in Indonesia or banking companies in other countries related to IFRS 9 implementation to compare the test results with this study.